Metode Bermain Sebagai Dasar Latihan Renang Anak: Persepsi Pelatih Renang di Samarinda - Novelius, Novelius; Sapulete, Jance Jacob; Huda, Muchamad Samsul; Satriana, Malpaleni; Kale, Sartika (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to find out how the play method is carried out as a swimming training process in early childhood seen from the perception of swimming coaches in Samarinda city. This research uses a qualitative method with a case study type to explore interconnected events. Data were collected through interviews with 12 swimming coaches, observation, and documentation for 4 months. The results of data analysis show that all swimming coaches use play methods in training early childhood swimming. Various kinds of play activities are applied so that children are happy and willing to follow the coach's instructions. The play method is applied through water games involving basic swimming movements, combining swimming techniques with games, creative activities, the use of skateboards and tools, as well as stories and imagination. Freestyle and breaststroke are prioritised as they do not require overly complex movements. Conclusion, Children aged 3-6 years are in an important gross motor development phase, where they begin to learn a variety of more complex physical skills, including freestyle and breaststroke swimming. Keywords:children's swimming training Play method, swimming coach's perception